2020
DOI: 10.1590/1806-9282.66.6.746
|View full text |Cite
|
Sign up to set email alerts
|

Can the neutrophil/lymphocyte ratio (NLR) have a role in the diagnosis of coronavirus 2019 disease (COVID-19)?

Abstract: SUMMARY OBJECTIVE The present study aimed to investigate the role of neutrophil/lymphocyte ratio (NLR), an inflammation marker, complete blood count, and biochemical parameters in the diagnosis of COVID-19. METHODS A total of 80 patients who had been hospitalized in the internal medicine clinic were enrolled in the study. The cases were allocated into two groups, i.e., COVID (+) and (-), based on real-time reverse transcription-polymerase chain reaction. The demographic, clinical, and laboratory [NLR, plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
73
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 19 publications
7
73
0
4
Order By: Relevance
“…Therefore, this biomarker is an indirect indication of the body's stress level due to the severity of the disease. This is also similar with findings from other studies where NLR was found to an important predictor of disease severity and outcome (3,(5)(6)(7)(8).…”
Section: Socio-demographic Comorbid Illness and Presenting Symptomssupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, this biomarker is an indirect indication of the body's stress level due to the severity of the disease. This is also similar with findings from other studies where NLR was found to an important predictor of disease severity and outcome (3,(5)(6)(7)(8).…”
Section: Socio-demographic Comorbid Illness and Presenting Symptomssupporting
confidence: 92%
“…Different laboratory markers are implicated as an indicator of disease severity, progression and outcome. Deranged cell counts, like anemia, polycythemia, leukopenia and leukocytosis with neutrophil predominance and decreased platelet count are found to be associated with severe disease and worse outcome in hospitalized patients (2)(3)(4)(5)(6)(7)(8)(9). Similarly raised liver enzymes and total bilirubin levels were identified in severe and critical patients (6,(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 96%
“…Recently, several studies have reported that NLR may differentiate between mild/moderate and severe/critical groups and probability of death in patients with COVID-19 infection. In addition, a series of studies have suggested NLR is a reliable predictor of COVID-19 progression and elevated NLR is associated with high mortality [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more and more studies have found that NLR is signi cantly different between the mild/moderate and severe/critical groups, survival and death group in COVID-19 patients. In addition, a series of studies have suggested NLR is a reliable predictor of COVID-19 progression and elevated NLR is associated with high mortality [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%